Analisis Strategi Bauran Promosi sebagai Upaya Meningkatkan Minat Beli Konsumen pada Produk Perusahaan Mikcout Project - Harri Ramdhani; Angga Nadiyanto Prastian (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the implementation of promotional mix strategies in increasing consumer purchase interest toward products offered by Mickout Project, a local fashion brand that focuses on streetwear apparel. In the midst of increasingly tight competition in the local fashion industry, effective promotional strategies are seen as key to building competitive advantage and fostering customer loyalty. The research employs a descriptive method with a qualitative approach. Data were collected through in-depth interviews, direct observations, and documentation involving the business owner, marketing team, and several active consumers of Mickout Project. The study focuses on how the five main elements of the promotional mix—advertising, sales promotion, public relations, personal selling, and direct marketing—are implemented in the brand's marketing practices. The results show that social media platforms, such as Instagram and TikTok, are the dominant promotional channels used to reach a young and wide audience quickly. Engaging visual content, collaborations with influencers, and seasonal promotional campaigns have proven effective in increasing brand awareness and consumer engagement. However, personal selling and direct marketing strategies have not yet been utilized to their full potential, even though they hold great promise for building closer relationships with customers. The findings indicate that the applied promotional mix strategies significantly contribute to increasing consumer purchase interest, especially when combined with quality products and competitive pricing. Therefore, the alignment between promotional efforts and product value plays a crucial role in influencing positive purchase decisions. In conclusion, the study finds that a targeted, consistent, and well-aligned implementation of the promotional mix strategy—tailored to the characteristics of the target market—can enhance consumer purchase interest and foster customer loyalty. The study recommends that Mickout Project develop a more integrated promotional strategy while strengthening personal approaches through direct marketing to deepen consumer relationships.